Ranking the competitiveness of the ruminant meat and meat preparation sub-sector amongst Asean countries - Ismail, Mohd Mansor; Abdullah, Amin Mahir; Hassanpour, Behrooz (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
The paper investigates the trade competitive positions of ASEAN countries for the meat and meat preparation sub-sector, specifically the ruminant category. The sub-sector has been chosen as it remains one of the main contributors to the food trade deficits in Malaysia despite the government’s promotion towards its production and consumption. This study, first examines the competitiveness of 20 food commodities in the meat and meat preparation sub-sector, namely the ruminant category (division 01) in Malaysia vis-à-vis selected ASEAN countries. We assess the competitiveness level by evaluating the Relative Trade Advantage (RTA). The indices are then used in pair wise comparisons to determine the countries’ competitiveness ranking. The data cover commodities in the HS 6 digits group over the period of 1998 to 2007. Thailand was ranked the highest in the sub-sector of meat and meat preparation for the ruminant category and Malaysia was ranked fifth.